Arab Islam di Indonesia dan India Adil Muhyid din Al Allusi; Penerjemah H Salin Basarahil; Penyunting Wiwik Sugiarji - ALALLUSI, Adil Muhyid Din; Basyarahil, H.Salim; Sugiarji, Wiwik (Gema Insani, 1992)
96 hlm. ; 18 cm.